Allied healthcare undergraduate education: international students at the clinical interface. Issue 3 (4th May 2017) - Morgan, Gareth
Abstract : The global movement of students in higher education is a relatively recent phenomenon, which has gained momentum in the last 30 years. Much research has been focused on the experiences of this population. Relatively little is known about international allied healthcare students who undertake clinical placements as part of their undergraduate course. This study explores students' perceptions of their clinical experience. The chosen focus group method was prefaced by a pilot study; both were conducted within the allied healthcare school of a university in the UK. Four themes emerged from the study: communication, cultural differences, relationships with professionals and survival strategies. Communication referred to both the interaction with and between the students, their patients and fellow members of the multidisciplinary team. Cultural differences were expressed in the negotiation of differing cultures at the patient interface. A third theme was the students' relationship with clinical professionals; within this, the relationship with the student's clinical educator was paramount. Finally, survival strategies represented the advice students wished to impart to future international students to facilitate their clinical placement abroad.